Iso 9000 Kalite Güvence Sisteminin Bir Tekstil Boyahanesine Uygulanışı - Sevdin, Göksenin G. (Fen Bilimleri Enstitüsü, 1998)
Günümüzde, değişen pazar ve hızla artan rekabetin etkisiyle, müşter isteklerine bağlı olarak kalitenin yönetimsel olarak uygulanması çalışmaları ön plana çıkmıştır.Önceleri kalite kavramı ve kalite kontrol, ürünün iyi ya da kötü olup olmadığım tanımlayan ve sadece ürünün ölçülebilen özellikleri ile ilgili bir kavramdı. Özellikle Endüstri devri-minden sonra teknolojinin hızlı artışı ve ürünlerin daha komplex bir yapıya dönüşmesi,o güne kadar ürün için uygulanan kalite kontrollerini etkisiz kıldı. Çözüm için ayrı departmanlar halinde organize edilen kalite kontrol bölümlerinin faaliyetleri de yetersiz kaldı. 1940'larda istatistiksel teknikleri geliştirilmesi ile, kalite kontrol ile ilgili metodlar geliştirildi. Bu yöntemlerin kullanım alanının yaygınlaştırılması için klavuz yayımlan-maya başlandı. Kalite kontrol için ilk standartlar yayımlandı. Kalite kontrol ile ilgili gelişmeler, kalitenin sadece belli bir departmana ait bir fonksiyon olmasının yeterli olmadığım gösterdi. Organizasyonların tüm bölümlerine kalite sorumlulukları veren ve kalitenin organizasyonun tüm yapısına yaygınlaştırıl ması gerektiğini savunan Toplam kalite kontrol kavramı gelişti. Toplam kalite kontrolünde, tüm organizasyonların, en alt seviyeden en üst seviyeye kadar kalite sorumlulukları vardır. Kalite güvence düşüncesi organizasyon yayılımlı Toplam Kalite kontrolü felsefesi ile ortaya çıktı. Kalitenin güvencesinde kalitenin tanımı sadece kullanıma uygunluk değil, müşteri istek ve beklentilerinin tatminidir. Bu işlem hizmet kalitesinin iyileştirilmesini de içerir. Kalite fâaliyetleri farklı grup, farklı kültürler tarafından ayrı ayrı ele alınıyordu. Kalite faaliyetlerinin tek bir dilden açıklanması için standartlar geliştirilerek yayımlandı. Zaman içerisinde yayımlanan bu standartların geliştirilmes ile birlikte en, son ISO (Uluslararası Sertifikasyon Organizasyonu) tarafından ISO 9000 Kalite Güvence Sistem standartları yayımlandı. Standardın, ISO 9001, ISO 9002, ISO 9003 şeklinde 3 farklı sistem modeli bulunmaktadır. Yazılı olan standardın uygulanması sırasında farklı etkiler görülebilir. Fason bir Tekstil Boyahanesine yapılan ISO 9002 uygulaması bu konuda bazı ipuçları verdi. ISO 9002 uygulama çalışmasında faaliyetler tek tek gözlendi. Sistem çalışması firmalar için kendi kendilerini kontrol edip geliştirme çalışmaları yapmak için fırsat verdi. Çoğu firma tarafından yapılan bu çalımşalar Toplam Kalite yönetimine geçiş için ön çalışma amacı ile yürütülür. Çalışmalar sırasında özellikle, sistem standartının tam anlaşılamamış olmasının firmalara ağır bürokrasi getirebileceği belirlenmiştir.

The object of the thesis is " Implementing Quality Assurance System ISO 9000 For A Textile Dyeing Mill " Nowadays,quality is common concept in all production and servicing industry. In compettive marketing circle, the importance and the issues of quality is increasing and the development on quality management systems is the main concept. The issue of quality is adapting to the custumer needs and expectations. At ancient times, the term of quality was making used in order to explain the product is good or not. This terms was about the mesured properties of the production. Quality and Quality Control is almost as old as the human race. In ancient times, Egyptians were involved in the earliest known formalized efforts to Quality Control. The perfections of the pyramids,attest to a conscious effort to control quality. Ancient Romans in artitecture, at the construction of the buildings, the effect of Quality Control can still be observed. Further evolution and developments of Quality Control ocurred in the follwing several basic stages : 1- Operator controlled quality of the product: Up to 1800s, the suppply of the services and production of the goods were limited to the single individuals or to a group of several persons. The quality results and quality standarts were self established. 2- Foreman controlled quality of the production: With the advent of industrilization, the complexity of manufacturing increased. This stage was called "Early Quality ". 3- Inspection quality control of the production: The growing technology resulted in a need to forms some groups of workers that performed inspections tasks. Organization began to realize the need for inspection and control individuals. The first inspection departments were not independent from production process. However,these groups of workers were not directly involved in the actual manufacturing and production. They were reported to the manufacturing department that whose efforts they were inspecting. In a period of time, inspection departments was changed into quality control departments that were active only in Quality Control on the product. 4- Statistical quality control of the product: Quality was controlled during production instead of being inspected into products. In a period of time, the inspections and Quality Control metods were not enough international interest in Quality Control were emerged Some national standarts were occured over Quality Control and statiscal metods. 5- Total quality control for production and servicing quality: The techniques were not applied to the serious Quality Control problems.Total Quality Control had the idea that all departmants not only the Quality Control department, had control responsibilities. Each department had some roles in occuring good quality. 6- Company wide quality control : Companywide Quality Control identifies the same phase as total Quality Control organizationwide. The most important difference from the other teories is that the highest level of management must be actively involved in Quality Control. And so quality became the responsibility of each individual. Companywide, Quality Management,is replacing Quality Assurance. The Quality Assurance departments is occured.These departments focuses on assuring the processes, product quality with operational audits, supplying training, performing analysis, applying quality improvement activities. Todays quality terms can be defined with the follwing activities: 1- Conformance to specifications and standarts. 2- Fitness to use 3- Satisfaction of custumer wants, expectations, at a competitive cost. Quality Management is the organizational function that responsible for defect preventation. Quality Management, recognizes the importance the broad systems issues if any organizations, and seeks effective ways to integrate the effort of large numbers of people with large numbers of machines and huge quantities of informatıon.lt now become, so critical to the survival of industry. Recognizing the need for diselimination of techinal knowledge,technical publications was recognized Up to ISO 9000 standarts, several standarts were published.ISO ( International Standarts Organization) developed standarts,so that there could be a common language and common understanding of concepts of quality. But ISO 9000 Quality Assurance system standarts is not a system that operates for verifying the conformance of organizations. ISO9000 standarts were first published in 1987 and revised and published in 1994 again. The primary aim of this standarts are to give organization quidelines on what constitutes an effective Quality Management system, which in turn can serve as a framework for continues improvement. The standart gives quidelines on the elements of Quality Management and quality system. XI The ISO 9000 family includes three quality assurance models: 1- ISO 9001: Quality systems- Model for Quality Assurance in design,development, production, installation,and servicing. 2- ISO 9002: Quality systems- Model for Quality Assurance in production,ınstallatıon and servicing. 3- ISO 9003: Quality systems- Model for Quality Assurance in last inspection and testing. Mostly..organizations engage the service of an independent quality system certification body to obtain ISO 9000 certificate of conformity. There are several causes for orginzations, in order to prefer certification: 1 -Product marketting advantage, 2- Cost advantage, 3- Motivation, 4- Custumer satisfaction. ISO 9001 Quality Assurance Systems model, consists of the follwing 20 quality management elments. 1- Management Responsibilities 2- Quality Systems 3- Contract Rewiev 4- Design Control 5- Documentation and Data Control 6- Purchasing 7- Custumer Supplied Product 8- Product Identification and Reliabilitiy 9- Process Control 10- Inspection and Testing 1 1- Control of inspection,Measurıng and Test Equipment 12- Inspection and Test Status 13- Control of Nonconforming Product 14-Corrective and Preventive Action 15- Handling, Storage, Packing 16- Quality Records 17- Internal Quality Audits 18- Training 19- Serciving 20- Statiscal Techniques Settinig up a ISO Quality Assurance System have some basic stages. In order to define theses stages, A practice over ISO 9002 quality systems in textile industry implementation for a knitted fabric dyenig ane finishing factory is observed The stages and steps of this ISO 9002 Quality Assurance System implementation researched are as the following: 1- Preview the condition of factory in order to begin for ISO 9002 system setting up. 2- Begining the training of the personnel about Qualiy Assurance Systems, ISO 9000 3- Constitution of project teams 4- Planning the project team's works. 5- Determination of existing condition. 6- Determination of working flow diyagrams; relations between departments. 7- Reviewing the organization, working descriptions. 8- Comparing the existing conditions and quality system elements of ISO 9002 9- Preparing a documentation system.Preparing quality manuals, Quality systems procedures. 10- Application the determined new activities. 11- Revising the prepared documentation system on order to change. 12- Corrective actions applied. xiii 13- Working with Quality Assurance System 14- Selecting the acceptance certification body 14- Perparatıon for certification audits The basic steps of an certification processes are: 1- A introduction gathering. 2- Reviewing the quality documentation system,; quality systems manuals, quality systems procedures 3- Sertificatıon audit. The fisrt step of an audit is reviewing the documantation system considering the connection with each other. The second step is controling the conformance of the apllicatıons. 4- At the result of the quality audits,after reviewing the application by the certification body, an decision is made.If it is conformance to the ISO 9002 quality system element reqirements, a certificate is given. On practices of ISO 9002 application, thruogh the working period,many difficulties was observed and received. These are: 1- At the begining of this working, the motivation and interesting for implemantation Quality Assurance System was not satisfied. 2- The related departments were not interested in order to determine, and prepare procedures, quality plans. 3- There was a lack of statiscally technique knowledge. The motive power for an organization for implementation ISO 9000 are: 1- A new start to reach total Quality Management 2- Demands from the customer 3- Improving product and servicing quality. 4- Improving the image of organization in market. ISO 900 implementation gives to the firm theses advantages: 1- Responding to the custumer request for ISO 9000 certificate. 2- Developing the service quality 3- Developing the relations with customers 4- Having commercial advantages.
Implementing Quality Assurance System Iso 9000 For A Textile Dyeing Mill
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Boyama; ISO 9000; Kalite güvence sistemi; Tekstil sektörü; Dyeing; ISO 9000; Quality assurance system; Textile sector